(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2021)
Cetacean remains have been recovered from archaeological sites all over Europe, but are especially abundant in Scotland. These remains originate from all periods and have often been worked into artefacts or tools, including chopping blocks, plaques, combs, pegs, snecks and perforated vertebral epiphyseal discs. It still remains unclear which species were exploited and to what extent active whaling was undertaken in the region. To address these questions Zooarchaeology by Mass Spectrometry (ZooMS) was undertaken on 35 cetacean specimens from five sites in Scotland (Jarlshof, Brough of Birsay, Quoygrew, Deerness and Freswick Links), dating from the Iron Age to the post-medieval period. Furthermore, morphological analysis was performed on the material in order to optimise the ZooMS identifications. A large variety of species were identified, including high numbers of Balaenidae sp and Globicephalinae sp. Comparison with other ZooMS studies in north-western Europe revealed equally high specimen numbers for these species, but also fin whale (Balaenoptera physalus), sperm whale (Phy-seter macrocephalus) and humpback whale (Megaptera novaeangliae). Moreover, one grey whale (Eschrichtius robustus) was identified in the Scottish specimens, adding to an increasing number of specimens indicating that the grey whale was once abundant in European waters. Furthermore, only one specimen of the common minke whale (Balaenoptera acutorostrata) was identified, despite modern stranding data which suggests this is the most common large whale species in Scottish waters. The large variety of species identified suggests that opportunistic scavenging was likely the primary method of acquiring cetaceans, though historical and ethnographic sources suggest that two distinct forms of active whaling may have occasionally been undertaken. The high number of Globicephalinae specimens from Jarlshof raise the possibility that drive-hunting might have already been undertaken at the site during the Iron Age.